Wild river - Deal, Borden 1922-1985; Huie, William Bradford 1910-1986; Osborn, Paul 1901-1988; Clift, Montgomery 1920-1966; Remick, Lee 1935-1991; Van Fleet, Jo 1914-1996 (Twentieth Century Fox Home Entertainment, 2012)
Montgomery Clift stars as Chuck Glover, a government agent who must evacuate a small town to make way for a new dam. When an elderly matriarch refuses to leave, Glover falls in love with her granddaughter, played by Lee Remick
Title from container
Originally released as a motion picture in 1960
Special features: Commentary by film historian Richard Schickel; original theatrical trailer
Keywords: Rührstück; Huie, William Bradford / 1910-1986 / Film adaptations; Deal, Borden / 1922-1985 / Film adaptations; Tennessee Valley Authority / Drama; Dams / Tennessee / Drama; Race relations / Drama; Deal, Borden / 1922-1985; Huie, William Bradford / 1910-1986; Tennessee Valley Authority; Dams; Race relations; Tennessee; Video recordings with Spanish language options; Video recordings with French language options; Drama; Feature films; Film adaptations; Video recordings for the hearing impaired; Vidéos pour personnes handicapées auditives; Film; DVD-Video